ANGKA PALING MUNGKIN DAN DETEKSI COLIFORM PADA SAMPEL LALAPAN DAUN KEMANGI (Ocimum bacilicum) DI KOTA PONTIANAK - Sari, Ita Purnama; Rahmawati, Rahmawati; Kurniatuhadi, Rikhsan (Jurnal Protobiont, 2019)
Ocimum basilicum is one type of vegetables that can be consumed without having to be processed. Food consumed must have high nutritional value, clean and free of microbes. Coliform is one of the bacteria that can cause disease in humans. This study aims to determine the value of MPN on samples Ocimum basilicumÂ leaves from warung lamongan in Pontianak and determine the existence of coliform bacteria on Ocimum basilicum leaf samples from warung lamongan in Pontianak. Detection of coliform bacteria using the MPN method. Detection of E. coli was carried out using EMBA media. The results showed that all samples had interval values between 210 MPN/g to > 1100 MPN/g. It showed that all samples excced the threshold determined by BPOM (2016), which was the maximum limit of coliform bacteria contamination in ready-toconsume vegetables was < 3 APM/g. The results of the identification of the bacterial genus coliform grouphad the members of genera Escherichia and Citrobacter